Comparison of Vertebrate Cytochrome b and Prepronociceptin for Blood Meal Analyses in Culicoides - Hadj-Henni, Leila; De Meulemeester, Thibaut; Depaquit, Jérôme; Noël, Philippe; Germain, Adeline; Helder, Remi; Augot, Denis (Frontiers in Veterinary Science, 2015)
To date, studies on host preferences and blood meal identification have been conducted for Culicoides species using molecular-based methods such as PCR techniques to amplify only a fragment from universal vertebrate mitochondrial genes such as Cytochrome C oxidase subunit I (COI) or Cytochrome b (Cyt b). The vertebrate prepronociceptin gene (PNOC) was also tested in this field. However, the choice of molecular marker to identify blood meal is critical. The objective of our study is to compare the ability of Cyt b and PNOC as molecular markers for blood meal identification depending on the stage of blood meal digestion. In order to determine whether these Cyt b and PNOC could provide a positive result, 565 blood-fed females of Culicoides spp were collected and morphologically identified. The samples were collected between 2012 and 2014, in two localities in France. The collection localities were near either livestock or a forest. To catch the specimens, we used UV CDC miniature light traps. PNOC sequence of donkeys (Equus asinus) was sequenced and submitted because it was missing in GenBank. Our findings emphasize that the PNOC marker is not suitable to separate closely related Equid species such as horses and donkeys. The Cyt b marker was able to identify 204 more samples when compared to PNOC (99.55% of specimens). Cyt b appears to be better able to detect the origin of blood meals from females with digested blood in their abdomens. We conclude that Cyt b is a good marker as it increases the accuracy of blood meal identification of engorged females containing digested blood in their abdomens. The host opportunist behavior of Culicoides, especially that of C. obsoletus and C. scoticus, the main vectors of BTV in Europe was also highlighted.